Private equity returns and disclosure around the world - Uwe Walz; Douglas Cumming (Goethe University Frankfurt, Center for Financial Studies (CFS), 2004)
We study the returns the venture capital and private equity investment from 221 venture capital and private equity funds that are part of 72 venture capital and private equity firms, 5040 entrepreneurial firms (3826 venture capital and 1214 private equity), and spanning 32 years (1971 - 2003) and 39 countries from North and South America, Europe and Asia. We make use of four main categories of variables to proxy for value-added activities and risks that explain venture capital and private equity returns: market and legal environment, VC characteristics, entrepreneurial firm characteristics, and the characteristics and structure of the investment. We show Heckman sample selection issues in regards to both unrealized and partially realized investments are important to consider for analysing the determinants of realized returns. We further compare the actual unrealized returns, as reported to investment managers, to the predicted unrealized returns based on the estimates of realized returns from the sample selection models. We show there exists significant systematic biases in the reporting of unrealized investments to institutional investors depending on the level of the earnings aggressiveness and disclosure indices in a country, as well as proxies for the degree of information asymmetry between investment managers and venture capital and private equity fund managers.
urn:nbn:de:hebis:30-10576
Keywords: G24; G28; G31; G32; G35; 330; Venture Capital; Private Equity; Risk; Return; Law and Finance; Aktienfonds; Risikokapital; Kapitalertrag; Portfolio-Investition; Portfolio-Management; Welt